Pengaruh E-Banking Dan Mobile Banking Terhadap Kinerja Keuangan Pada Perbankan Konvensional di Kota Padang - Suci Ramadhani; Enny Arita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyze the effect of E-Banking and Mobile Banking usage on the financial performance of conventional banks in Padang City, both partially and simultaneously. The research population consists of employees in the operational, financial, and digital service divisions of conventional banks in Padang City, while a sample of 80 respondents was selected through purposive sampling based on criteria relevant to the research variables. This study employs a quantitative approach using primary data collected through questionnaires. Data analysis was conducted using multiple linear regression, the coefficient of determination, t-test, and F-test with the assistance of SPSS version 26 software. The results indicate that E-Banking has a positive and significant effect on the financial performance of conventional banks in Padang City, and Mobile Banking also has a positive and significant effect on financial performance. E-Banking and Mobile Banking simultaneously influence financial performance. The influence of both independent variables on financial performance is 53.8%.